Os campos de experiência nas aulas de educação física na educação infantil: narrativas de um professor pesquisador - Assis, Luiz Henrique do Nascimento (Universidade Federal de São Carlos, 2026)
This research emerged from the researcher's teaching trajectory and engaged with normative documents in the field, the Brazilian National Common Curriculum Base (BNCC, 2017), and studies that discuss space as a pedagogical element. Therefore, the objective of this research was to understand the process of developing and implementing a didactic unit, carried out in spaces "beyond the sports court," in Physical Education classes for students in Early Childhood Education, considering its articulation with the fields of experience foreseen in the BNCC (2017). Methodologically, a teacher-researcher's narrative was used as a qualitative approach, through classroom diaries produced after each intervention, video recordings, and systematic observations of daily school life. This study was developed in a Municipal Early Childhood Education School (E.M.E.I.) of the Municipal Education Network of Carapicuíba, located in the State of São Paulo. The target audience for the research was the Preschool II classes, with children aged 4 to 5 years and 11 months, comprising 40 children in the research group. The results showed that the use of spaces beyond the playground, such as the patio, lawn, corridors, and outdoor areas, expanded the pedagogical possibilities of Physical Education in Early Childhood Education. The children demonstrated high engagement, creativity, autonomy, and the ability to reinterpret environments, while developing motor, expressive, and socio-emotional skills foreseen in the BNCC (2017) Fields of Experience. The analyses also revealed that physical space, when understood as a pedagogical object, acts as a mediator of interactions, playful exploration, and the construction of meaning by children. The narrative writing of the teacher-researcher was configured as a central formative and analytical tool, allowing the identification of nuances in the educational process, daily challenges, and opportunities for pedagogical reinvention. Among the main challenges, the structural limitations of school spaces, the constant need for methodological adaptations, and the interferences resulting from sharing environments with other classes stood out. Even so, these challenges did not compromise the objectives of the proposal; on the contrary, they reinforced the importance of teacher intentionality and the valuing of childhood culture. It is concluded that pedagogical practice that extends "beyond the playground" promotes meaningful and contextualized bodily experiences, contributing to the integral development of children and to the strengthening of Physical Education in Early Childhood Education. The research points to the need for institutional investment in qualified environments, as well as for the development of new investigations that explore different scenarios, participatory methodologies, and the voice of the children themselves.
The fields of experience in physical education classes in early childhood education: narratives from a teacher-researcher
Keywords: Educação Física Escolar; Educação Infantil; Campos de Experiência; Espaços; Narrativas; School Physical Education; Early Childhood Education; Fields of Experience; Spaces; Narratives; CIENCIAS DA SAUDE::EDUCACAO FISICA; 4. Educação de Qualidade